Selective activation of the prostaglandin E2 receptor subtype EP2 or EP4 leads to inhibition of platelet aggregation - Kuriyama, Shuhko; Kashiwagi, Hitoshi; Yuhki, Koh-ichi; Kojima, Fumiaki; Yamada, Takehiro; Fujino, Takayuki; Hara, Akiyoshi; Takayama, Koji; Maruyama, Takayuki; Yoshida, Akitoshi; Narumiya, Shuh; Ushikubi, Fumitaka (Thrombosis and Haemostasis, 2010)
The effect of selective activation of platelet prostaglandin (PG) E2 receptor subtype EP2 or EP4 on platelet aggregation remains to be determined. In platelets prepared from wild-type mice (WT platelets), high concentrations of PGE2 inhibited platelet aggregation induced by U-46619, a thromboxane receptor agonist. However, there was no significant change in the inhibitory effect of PGE2 on platelets lacking EP2 (EP2–/– platelets) and EP4 (EP4–/– platelets) compared with the inhibitory effect on WT platelets. On the other hand, AE1–259 and AE1–329, agonists for EP2 and EP4, respectively, potently inhibited U-46619 -induced aggregation with respective IC50 values of 590 ± 14 and 100 ± 4.9 nM in WT platelets, while the inhibition was significantly blunted in EP2–/– and EP4–/– platelets. In human platelets, AE1–259 and AE1–329 inhibited U-46619-induced aggregation with respective IC50 values of 640 ± 16 and 2.3 ± 0.3 nM. Notably, the inhibitory potency of AE1–329 in human platelets was much higher than that in murine platelets, while such a difference was not observed in the inhibitory potency of AE1–259. AE1–329 also inhibited adenosine diphosphate-induced platelet aggregation, and the inhibition was almost completely blocked by AE3–208, an EP4 antagonist. In addition, AE1–329 increased intracellular cAMP concentrations in a concentration- and EP4-dependent manner in human platelets. These results indicate that selective activation of EP2 or EP4 can inhibit platelet aggregation and that EP4 agonists are particularly promising as novel anti-platelet agents.
Keywords: Platelet aggregation; prostaglandin E2; EP2; EP4; anti-platelet agent